Navigating Troubled Waters: Evaluating the Function and Material Legitimacy of European Criminal Law (Polish Yearbook of International Law, 2024)
The question of the function of European criminal law has dominated recent doctrinal thinking. In order to answer that question, a thorough study on the guiding principles of criminalisation and their applicability to the European Union’s legislative process was necessary. This article focusses first on the concept of legitimacy and the need for a European criminal policy, and then on some principles that already exist in the EU’s legal order and their ability to provide said legitimacy. Following the conclusion that the existing principles are insufficient, it is suggested that the harm principle and the principle of protection of legal goods would be more appropriate to evaluate the material legitimacy of European criminal law. For that purpose, the multiple categories of interests that coexist in the EU will be analysed according to the allocation of responsibility for their protection. That distinction will, in turn, lead to the proposal of a three-step process to assess any given instance of criminalisation stemming from the EU. Finally, the practical consequences of such a process will be mentioned in the conclusion.